Penerapan penilaian otentik dalam pembelajaran tema peduli terhadap makhluk hidup pada kelas IV sekolah dasar - Annisa Puspitaning Tiyas; Chumdari Chumdari; Karsono Karsono (Universitas Sebelas Maret, 2021)
The purpose of this research was to find out about the application of authentic assessment in the Ta'mirul Islam Surakarta Elementary School, and to determine the extent of the suitability between the applied authentic assessment and the Assessment Guidelines for Elementary Schools.This research is a descriptive qualitative research. The main subjects in this research were teachers of grade four H and the main object was an assessment document. Data collection techniques used were observation, interview, and document study techniques. Data validity in this research used data triangulation techniques. Analysis of the data used in this research is to use data analysis model of Miles and Huberman.The results of this research is The teacher applied three aspects of assessment. First, afektif aspect uses observation, self, and peer assessment techniques. Second, kognitif aspect uses written test assessment techniques, oral tests, and assignments. Third, psikomotor aspect uses performance and project assessment techniques. The conclusion of this research is that teachers have implemented an assessment of the 2013 Curriculum based on the Assessment Guidelines for Primary Schools published by the Ministry of Education and Culture, but not all of them have been implemented in practice.